PENGARUH FASILITAS BELAJAR DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN IPS KELAS VIII SISWA SMP NEGERI 5 PEKANBAU - M. Yogi Praminto; Gimin Gimin; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstrack: this study aims to determine the effect of learning facilities and learning interest on student learning outcomes in class VIII social studies learning. As for the things that want to be discussed in this study is: how learning facilities and student learning interests affect student learning outcomes in social studies class VIII at SMP Negeri 5. The research sample was taken by 76 respondents. The results of this study are learning facilities and students' learning interest have a positive effect on student learning outcomes and lead to good learning outcomes. With R2 (Square) learning facilities and interest in learning have an influence of 28.5% on student learning outcomes at SMP 5. The remaining 71.5% are influenced by other factors. Therefore, there is an influence between facilities and learning interest on student learning outcomes at SMP 5 Pekanbaru.Key Words: Learning Facilities,Learning Interest, Learning Outcomes